THE HISTORY OF UZBEKISTAN: A LAND AT THE CROSSROADS OF CIVILIZATIONS - Daminova Asila,; Islomova Gulshoda, (Ustozlar uchun, 2025)
This article provides a concise overview of the rich and diverse history of Uzbekistan, a Central Asian country located at the crossroads of ancient civilizations. It explores the evolution of the region from early settlements in the Neolithic era to its role in major empires such as the Achaemenid, Greco-Bactrian, Kushan, and Timurid. The article highlights the country’s cultural and scientific achievements, especially during the Islamic Golden Age, and discusses the impact of Soviet rule and the path to independence. Emphasis is placed on Uzbekistan’s continuous development and its efforts to balance historical heritage with modern progress.